Content and Meaning of Financial Cyber Security: a Bibliometric Analysis - Vitaliia Koibichuk; Tetiana Dotsenko (Financial Markets, Institutions and Risks)
Reliable cybersecurity has a decision value for economic and national security of every country. The financial sector is most susceptible to cyber-attacks, as it is one of the most important systems of society, containing a large amount of data and critical information. To provide reliable cybersecurity, government must participate actively in development and strengthening of policies. It includes establishment of rules and standards for business, creation of only national strategy of cybersecurity and participating in international partnership for an exchange advanced experience and resources. In addition, government must invest in cybersecurity tools, technology, and personnel to protect digital infrastructure and the data of citizens and companies. Finally, governments should prioritize cyber security education and awareness among citizens and companies to minimize the risk of digital attacks. The article provides a comprehensive bibliometric analysis of scientific publications devoted to the topic of financial cyber security using modern powerful bibliometric software (Vosviewer, Bibliometrix, SciVal) and an analysis of normative legislative documents of Ukraine and the European Union, in particular the recommendations of the European Union Agency for Cyber Security (ENISA). The bibliometric analysis made it possible to form groups of clusters characterizing the cyber lexicon, methods, and technologies for detecting cyberthreats, and to highlight the most cited publications in the world. The statistical basis for the analysis was formed by scientific publications indexed by the Elsevier reference and bibliographic corporation. The results of the conducted research are a plan of recommended actions for managers of financial institutions, banks, and enterprises regarding the effective organization of cyber security and includes such steps as: development of cyber security culture on an ongoing basis; appointment of a responsible person for the organization of cyber security; conducting cyber security audits on an ongoing basis; creating a data protection memo; provision of advanced training in the field of cyber data protection; ensuring effective interaction with a third party involved in financial relations, reflected in concluded contracts; formation of a response plan to cyber incidents; organization of secure access to automated information systems used in the institution's operations; organization of device security in case of remote use and performance of professional duties; organization of network connection security; improvement of physical security of official documents and devices; protection of backup copies and testing for the possibility of a full update based on these backup copies; synchronization with cloud technologies in compliance with the provisions of regulatory documents; protection of websites, publication and distribution of up-to-date information on new types and types of cyber threats.